2018
DOI: 10.18805/ijar.b-792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of palm kernel shell ash as organic mineral supplement on performance of broiler chicks

Abstract: Evaluation of palm kernel shell ash (PKSA) as organic mineral supplement on broiler chicks performance was conducted. Ninety six Arbor Acre day old chicks were randomly assigned in 3 replicates of eight birds per replicate to four experimental diets containing graded levels of PKSA at 0, 5,10 and 15kg/ton of feed labeled T 1 , T 2 , T 3 and T 4 respectively. At 1 st week of life, the chicks were assessed for growth performance, digestive tract development, histology and digesta pH. The growth performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Results showed 69 % removal efficiency of β-carotene from the crude palm oil. In animal husbandry, feedstock was made from PKS (Ohanaka et al, 2021). They made a good blend of PKS with pig dung and bamboo chips to formulate activated charcoal recommended as livestock feed additive.…”
Section: Application Of Pks In Agriculturementioning
confidence: 99%
“…Results showed 69 % removal efficiency of β-carotene from the crude palm oil. In animal husbandry, feedstock was made from PKS (Ohanaka et al, 2021). They made a good blend of PKS with pig dung and bamboo chips to formulate activated charcoal recommended as livestock feed additive.…”
Section: Application Of Pks In Agriculturementioning
confidence: 99%
“…As well, the diet supplemented with 24% sugar beet pulp can significantly increase the number of bifidobacteria and lactobacilli in growing pig intestines and reduce the number of E. coli In case of compared with the basic diet group (Laitat et al 2015). So, the possible reasons for the ability fiber to change the number of microorganisms in pig intestines depend on the developed of the villi, pH values and metabolic processes in the GIT, thereby improving absorption of nutrients as a result of the larger intestinal surface areas (Ohanaka et al, 2018). On the other hand, Fiber can be used as a substrate for some microorganisms and natural antioxidant (Riar and Paul, 2017).…”
Section: The Effect Of Dietary Fiber On the Number Of Pig Intestinal Floramentioning
confidence: 99%
“…The villus length increased significantly in both 50 µg/kg and 100 µg/kg groups (P<0.05; Table 2, Fig 1) and the higher the villi and their densities, the larger the surface area for digestion and absorption. (Ohanaka et al 2018). In addition, we observed that the The data is expressed as mean±standard deviation (n=4).…”
Section: Effects Of Exogenous Ghrelin On the Duodenum Morphology Of A...mentioning
confidence: 99%